2008
DOI: 10.1016/j.biopsych.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-Methyltransferase Contributes to Genetic Susceptibility Shared Among Anxiety Spectrum Phenotypes

Abstract: Background-Catechol-O-methyl transferase (COMT) has been investigated for its possible role in a wide range of psychiatric phenotypes. In particular, several studies support association of this gene with panic disorder and other anxiety-related traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 66 publications
3
77
1
1
Order By: Relevance
“…One gene implicated in a number of mental health disorders including depression is catechol-O-methyltransferase (COMT), a gene which regulates catecholamine's like dopamine, epinephrine, and norepinephrine in the brain (Gogos et al 1998). Among individuals with specific COMT genotypes and a history of stressful life events, polymorphisms might increase their risk of developing anxiety spectrum disorders, depressive illness, obsessive compulsive disorder, schizophrenia or alcohol dependence (Mandelli et al 2007;Hettema et al 2008;Wray et al 2008;Voisey et al 2011;Voisey et al 2012). Our understanding of these interactions is limited despite the growing evidence that inter-individual genetic variability can moderate an individual's vulnerability or resilience to the effects of stressful life events (SLEs) and subsequent mental health problems (Kendler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One gene implicated in a number of mental health disorders including depression is catechol-O-methyltransferase (COMT), a gene which regulates catecholamine's like dopamine, epinephrine, and norepinephrine in the brain (Gogos et al 1998). Among individuals with specific COMT genotypes and a history of stressful life events, polymorphisms might increase their risk of developing anxiety spectrum disorders, depressive illness, obsessive compulsive disorder, schizophrenia or alcohol dependence (Mandelli et al 2007;Hettema et al 2008;Wray et al 2008;Voisey et al 2011;Voisey et al 2012). Our understanding of these interactions is limited despite the growing evidence that inter-individual genetic variability can moderate an individual's vulnerability or resilience to the effects of stressful life events (SLEs) and subsequent mental health problems (Kendler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This functional variant in the coding sequence of COMT gene has attracted a number of studies in various PD-related phenotypes (see Table 1). 22,[120][121][122][123][124][125][126][127] A recent meta-analysis of six available case-control studies showed significant association of the COMT 158 Val allele with PD in the Caucasian samples and, conversely, a trend toward association of the COMT 158 Met allele with PD in the Asian samples. 128 Interestingly, stratification for gender as well as ethnicity revealed that the associations of the 158 Val allele in Caucasians and, reciprocally, the 158 Met allele in Asians were restricted to females.…”
Section: Chromosome 22mentioning
confidence: 99%
“…Notably, positive associations detected for several genetic polymorphisms in PD were also found in schizophrenia, 133 depressive disorders, 18,24,113,134 bipolar disorder, 59,135 and other anxiety disorders, or anxiety-related personality traits. 21,24,86,127 Accordingly, linkage studies have shown a chromosomal overlap between PD and other anxiety phenotypes, 10 MDD, 136 and bipolar disorder. 137 This may indicate that some genetic variants confer a general susceptibility to several syndromes or personality traits, rather than a specific susceptibility to any particular disorder.…”
Section: Interpretation Of Linkage and Candidate Gene Studiesmentioning
confidence: 99%
“…Many studies have investigated the contribution of COMT gene SNPs in some disease conditions [7,9]. The role and relevance of individual COMT SNP on musculoskeletal pain may vary if other SNPs also contribute to it especially, when they are nearby and in linkage disequilibrium with the functional SNPs.…”
Section: Introductionmentioning
confidence: 99%